Thrombospondins Differentially Regulate Proteins Involved in Arterial Remodeling - Kassem, M M; Helkin, A; Maier, K G; Gahtan, V (Physiological research, 2019)
Thrombospondins (TSPs) are matricellular glycoproteins expressed in response to vascular injury. TSP-1 and TSP-2 are promotors of arterial remodeling while TSP-5 is believed to be protective. The current study assessed the differential effect of TSPs on protein expression in vascular smooth muscle cells (VSMCs). We hypothesized that TSP-1, TSP-2 and TSP-5 would regulate VSMC proteins involved in arterial remodeling. Human VSMCs were exposed to TSP-1, -2, -5 or serum free media (24 hours). Cell lysates were used to assess the targets TSP-1, TSP-2, TSP-5 and CD44), while the culture media was used to detect TGF-ß1, PDGF-BB, ANGPTL-4 and IL-8. Statistical analysis was performed by t-test and p< 0.05 was considered significant. All TSPs increased their own expression and TSP-5 increased TSP-2. TSP-1 and TSP-2 increased production of ANGPTL-4 and PDGF-BB, while TSP-5 only increased ANGPTL-4. TSP-1 increased exclusively TGF-ß1 and CD44 production. TSP-2 increased TSP-1 expression. All TSPs decreased IL-8. The findings suggest that TSP-1 and TSP-2 may promote vascular remodeling, in part, by increasing ANGPTL-4, PDGF-BB and their own expression. TSP-5 did not upregulate the inflammatory mediators TSP-1, PDGF-BB or TGF-ß1, but upregulated its own expression, which could be a protective mechanism against the response to vascular injury.
Keywords: thrombospondin 1; Myocytes, Smooth Muscle; thrombospondiny; Thrombospondins; Cartilage Oligomeric Matrix Protein; Vascular Remodeling; Muscle, Smooth, Vascular; kultivované buňky; Cells, Cultured; chrupavkový oligomerní matrixový protein; arterie; Arteries; lidé; myocyty hladké svaloviny; svaly hladké cévní; remodelace cév; Humans; Thrombospondin 1